THE EDUCATIONAL POTENTIAL OF THE ORTHODOX FAITH ABOUT THE "LIVING" - Horban, Olexandr (Educological discourse, 2017)
The author presents an author's approach to the philosophical interpretation of the phenomenon of "living" in the Orthodox discourse through the prism of the educational potential of Orthodox teachings. In particular, it is noted that education, as a single system of interrelated processes of education and upbringing, when forming a harmonious, highly spiritual personality, turns its attention not only to the scientific fact of knowledge, but also appeals to other, unscientific worldview elements of human existence. Among them, the undisputed leader is religion. The Christian doctrine of the "living", as the creative beginning of being, can be claimed as certain educational reflections in the course of the educational processes of the formation of an integral human personality. A significant heuristic potential for the study of this phenomenon is the modern Orthodox discourse of the indicated problems. The modern educational paradigm, focusing not so much on the quantitative transfer of the amount of knowledge, but rather on the education of a harmonious person, for which the formation of the axiological component of new knowledge is more important, is significantly in touch with modern religious beliefs about the need for education through the education of a highly moral person. In particular, today in the Orthodox theological discourse increasingly shifts the emphasis in the problem of understanding the living: from the ontological and epistemological to the axiological and moral. Christianity is oriented toward personal salvation, that is, the salvation of the human soul and its eternal presence in paradise. And in order to achieve this, a person must adhere to certain rules and guidelines that make up the essence of Christian Orthodox ethics. Therefore, given the scientific inconsistencies in the ethical and legal nature of the relative concept of the "living" in the context of scientific and technological progress, a return to the syncretic foundations of human knowledge, to reason as wisdom, in which rational and cognitive is connected with practical philosophy, is of some importance. And the corresponding Orthodox doctrines acquire a significant educational potential, with the application of which in the educational process the goal of the formation of a harmonious, highly spiritual personality.